ANALYSIS OF CRIMINAL LIABILITY OF CHILDREN AS PERPETRATORS OF AGGRAVATED THEFT (A STUDY OF DECISION NUMBER 19/PID.SUS-ANAK/2025/PN.MGL) - Yunialba Tibrizi Triu Usman; Baharudin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
One crime involving children as perpetrators is the crime of theft under aggravating circumstances, as decided by the Menggala District Court in Case Number 19/Pid.Sus-Anak/2025/PN.Mgl with a child defendant. The question is: What are the factors that cause children to commit the crime of theft under aggravating circumstances based on Decision Number 19/Pid.Sus-Anak/2025/PN.Mgl? And how are children held accountable as perpetrators of the crime of theft under aggravating circumstances based on Decision Number 19/Pid.Sus-Anak/2025/PN.Mgl? The research method is through a normative legal approach and an empirical approach using secondary and primary data. Next, a qualitative legal data analysis was conducted, namely by describing the resulting data in the form of explanations or sentence descriptions arranged systematically. The results of the study, that the factors causing children to commit the crime of theft under aggravating circumstances based on Decision Number 19/Pid.Sus-Anak/2025/PN.Mgl include an environment that provides opportunities to commit crimes, a social environment that provides examples and role models and an economic environment, poverty and misery. The responsibility of the child as the perpetrator of the crime of theft under aggravating circumstances based on Decision Number 19/Pid.Sus-Anak/2025/PN.Mgl was declared legally and convincingly proven guilty of violating Article 363 paragraph (1) 4th and 5th of the Criminal Code with a sentence of imprisonment in a Special Child Development Institution (LPKA) for 1 (one) month. Parents are advised to monitor their children's behavior, especially regarding the negative impacts of social interactions in their neighborhood, thereby minimizing the occurrence of aggravated theft by children.